Intellectual Property Rights: A Study of Copyright Regulation in Indonesia in The Perspective of Positive Law and The Value of Benefit - Rio Pradita Wibowo; Jasmine Fahira Maulana; Yenny Ratnasari; Mutiara Dewi Lazha; Rakhul Akbar Maulana; Diana Setiawati (Proceeding International Conference Restructuring and Transforming Law, 2025)
Intellectual Property Rights (IPR) are exclusive rights granted to individuals or groups for their creative works that benefit society. They protect interests, financial rights, and prevent infringement. This research aims to find out how the regulations in Indonesia and its benefits in the registration of Intellectual Property Rights, especially Patent Rights. This research uses normative juridical research to analyze legal issues using various legal materials. It focuses on positivistic views, principles, doctrine, discovery, systematics, harmonization, comparative studies, and history. The approach includes statutory and conceptual analysis, grammatical and systematic interpretation. Copyright protection in science, art and literature often coincides with creation, where the creator does not register the work. Indonesian copyright law uses principles such as lex posterior derogat legi priori. Islamic jurisprudence emphasizes intellectual property rights and the prohibition of unlawful consumption, the researcher draws from a concept namely Maqashid As-Sharia. The Maqashid as-Sharia approach, which focuses on the benefit of protecting the mind and property, can be used to study intellectual property rights in Islamic law. In this case, it is expected that the creators can register their creations for the sake of the formation of benefits.